Black magic: religion and the African American conjuring tradition - Chireau, Yvonne Patricia (University of California Press, 2003)
This work looks at the origins, meaning and uses of Conjure - the African American tradition of healing and harming that evolved from African, European and American elements - from the slavery period to well into the 20th century. The author rewrites the dichotomy between magic and religion